The minimalist program - Chomsky, Noam (The MIT Press, 2015)
In his foundational book published in 1995, the author offered a significant contribution to the generative tradition in linguistics. This twentieth-anniversary edition reissues this classic work with a new preface by the author. The author attempts to situate linguistic theory in the broader cognitive sciences, with the chapters formulating and progressively developing the minimalist approach to linguistic theory.
Keywords: Minimalist theory (Linguistics); Minimalisme (Linguistique); LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Historical & Comparative.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General.; LINGUISTICS & LANGUAGE/General